Selective maintenance optimization for series-parallel systems with continuously monitored stochastic degrading components subject to imperfect maintenance - Khatab, A.; Aghezzaf, E.H. (IFAC-PapersOnLine, 2016)
This paper addresses a degradation-based selective maintenance decision problem in a continuously monitored multi-component system, carrying out several missions with scheduled inter-mission breaks. Each system’s component is modeled as a time-dependent stochastic process. Each component is also assigned a list of maintenance actions ranging from imperfect maintenance actions up to complete overhauling. Both corrective and preventive imperfect maintenance are allowed. To improve the probability of the system successfully completing the next mission, maintenance is performed on the system’s components during the break. The selective maintenance problem aims thus at finding a cost-optimal subset of maintenance actions, to be performed on the system during the limited duration of the break, which guarantees the successful completion of the next mission with a minimum reliability level. The fundamental constructs and the relevant parameters of this new nonlinear selective maintenance optimization problem are developed and thoroughly discussed. A numerical example is provided to illustrate the proposed approach.